Kajian tentang Bagaimana Brand Image, Kualitas Produk, serta Harga Memengaruhi Loyalitas Pelanggan terhadap Produk Skincare MS Glow - Eko Sugiono; Pujianto Pujianto; Yudhi Perdana; Dedi Triono; Darmono Darmono; Muhammad Bayu; Djupiansyah Ganie; Yohanes Sri Guntur (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
The purpose of the research was to find out and analyze the Influence of Brand Image, Product Quality and Price on Consumer Loyalty in Ms Glow Skincare Products in Berau Regency. This study was conducted on 85 Ms Glow skincare users in Berau Regency as respondents using the purposive sampling method. The analysis tools used are: Validity Test, Reliability Test, Multiple Linear Regression Analysis, Correlation Coefficient, Determination Coefficient, T Test and F Test. Based on the results of the study, it can be seen that the results of the T Test show that the variables of Brand Image, Product Quality and price partially have a significant effect on the variables of consumer loyalty. Then based on the F test, it is known that the variables of Brand Image, Product Quality and price simultaneously have a significant effect on the variables of consumer loyalty. Then, based on the determination coefficient (R Square) of 0.796 (79.6%). This illustrates that the variables of Brand Image, Product Quality and Price are able to influence the Consumer Loyalty variable in Ms Glow skincare products in Berau Regency by 79.6% while the remaining 20.4% is explained by other factors that are not included in this study.